KEKUATAN POLITIK ZULKIFLI AS – EKO SUHARJO DALAM PEMENANGAN WALIKOTA DUMAI TAHUN 2015 - Elipati Simorangkir; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Zulkifli AS not only served as the District Head in East Dumai even occupied important seats in government circles Dumai but never as Mayor of Dumai 2005-2010. Men who are having a lot of experience in the government bureaucracy Dumai encourage local people on the election of Mayor of Dumai 2015 to give voting rights to participation and Zul AS. Moreover Zul As paired with a young leader native of Dumai, Eko Suharjo. Who also has experience in the field of legislation. Eko Suharjo who had served as Vice Chairman of the Parliament Dumai and has also become a member of the Provincial Parliament. The capacity and quality of this couple in the lead Dumai be in determining the size of the community leaders. The authors are interested to see the political forces in winning Zulkifli AS - Eko Suharjo and political strategy carried out in the election Mayor of Dumai 2015.The concept used is the political power, political strategy, and the concept of election. The author conducted research with descriptive analysis method with basic qualitative research studies. Retrieval of data obtained from the primary and secondary data collection with in-depth interviews. Data from interviews are recorded as carefully as possible and collected. All data were analyzed qualitatively so that what is contained behind reality can be revealed as soon as possible.These results indicate that the support of political forces in the election Mayor of Dumai namely the influence of the coalition party concerned Dumai, interest groups, media and political figures. In addition, Zulkifli As a figure of the achievements and wealth of experience in the bureaucracy accompanied by a cadre of political party best marked by success into DPRD Kota Dumai and Members of Parliament the provincial level as well as strategies that are run by team is winning that drove the pair Zulkifli AS - Eko Suharjo as winner in the election of Mayor and Vice Mayor of Dumai, 2015.Key Words: The Politics Power, Political Strategy, Election